Modulation of pulsed electric field induced oxidative processes in protein solutions by pro- and antioxidants sensed by biochemiluminescence - Červinková, Kateřina; Vahalová, Petra; Poplová, Michaela; Zakar, Tomáš; Havelka, Daniel; Paidar, Martin; Kolivoška, Viliam; Cifra, Michal (Scientific reports, 2024)
Technologies based on pulsed electric field (PEF) are increasingly pervasive in medical and industrial applications. However, the detailed understanding of how PEF acts on biosamples including proteins at the molecular level is missing. There are indications that PEF might act on biomolecules via electrogenerated reactive oxygen species (ROS). However, it is unclear how this action is modulated by the pro- and antioxidants, which are naturally present components of biosamples. This knowledge gap is often due to insufficient sensitivity of the conventionally utilized detection assays. To overcome this limitation, here we employed an endogenous (bio)chemiluminescence sensing platform, which enables sensitive detection of PEF-generated ROS and oxidative processes in proteins, to inspect effects of pro-and antioxidants. Taking bovine serum albumin (BSA) as a model protein, we found that the chemiluminescence signal arising from its solution is greatly enhanced in the presence of H 2 O 2 as a prooxidant, especially during PEF treatment. In contrast, the chemiluminescence signal decreases in the presence of antioxidant enzymes (catalase, superoxide dismutase), indicating the involvement of both H 2 O 2 and electrogenerated superoxide anion in oxidation-reporting chemiluminescence signal before, during, and after PEF treatment. We also performed additional biochemical and biophysical assays, which confirmed that BSA underwent structural changes after H 2 O 2 treatment, with PEF having only a minor effect. We proposed a scheme describing the reactions leading from interfacial charge transfer at the anode by which ROS are generated to the actual photon emission. Results of our work help to elucidate the mechanisms of action of PEF on proteins via electrogenerated reactive oxygen species and open up new avenues for the application of PEF technology. The developed chemiluminescence technique enables label-free, in-situ and non-destructive sensing of interactions between ROS and proteins. The technique may be applied to study oxidative damage of other classes of biomolecules such as lipids, nucleic acids or carbohydrates.
Keywords: Reactive Oxygen Species; oxidace-redukce; Luminescence; katalasa; Antioxidants; Hydrogen Peroxide; Catalase; sérový albumin hovězí; luminiscence; luminiscenční měření; Animals; Luminescent Measurements; antioxidancia; peroxid vodíku; zvířata; Cattle; elektřina; skot; reaktivní formy kyslíku; Oxidation-Reduction; Electricity; Serum Albumin, Bovine